Horn colour varieties of the Hungarian Grey cattle - Radácsi, Andrea; Bodó, Imre; Béri, Béla (Acta Agraria Debreceniensis, 2008)
The Hungarian Grey Cattle breed is a ‘success-story’ of the national genetic conservation work. Traits of the breed have been subjects of several research projects, although many relationships remained unclear. Our present research results were meant to call attention to a less emphasized trait of the breed: the different horn colour varieties. Research work was carried out in the Hungarian Grey stock of the Hortobágy Non-profit Company for Nature Conservation and Gene Preservation. Ratio of the three main horn colour varieties (white, ‘cardy’, green) were determined in the observed female, male and steer stocks. Our results showed no significant differences (P<0,05) in the distribution of the horn colour varieties of the female and bull stocks, and of the female and steer stocks. We found that on the basis of the ratio of white colour, four sub-categories can be distinguished within the ‘cardy’ colour variety. Results of the statistical analysis (P<0,05) confirmed that the colour of the horn and the ratio of the black part on the horn tip are two different traits.